Analisis Pengaruh Kepekatan Asap Terhadap Waktu Respon Alat Pendeteksi Asap Berbasis Arduino - Ridho Ilham; Asrori Asrori (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
Work safety is always a priority, especially in the mining world which has a high potential for danger. Therefore, there are many regulations that must be obeyed, including the prohibition of smoking in the cabin of the Dump Truck unit. This study aims to design a cigarette smoke detector in the cab of a dump truck as a form of warning to drivers who violate the ban on smoking in the cab. The method used in this research is a quantitative method by conducting experiments. The research conducted is to analyze the effect of smoke thickness levels (20%, 40%, and 60%) on different sensor types (MQ-4 and MQ-7). The expected result is the effect of smoke thickness variation on the response time of different sensors.